2003
DOI: 10.1017/s0022112003006268
|View full text |Cite
|
Sign up to set email alerts
|

The effect of numerical errors and turbulence models in large-eddy simulations of channel flow, with and without explicit filtering

Abstract: Turbulent channel flow simulations are performed using second- and fourth-order finite difference codes. A systematic comparison of the large-eddy simulation (LES) results for different grid resolutions, finite difference schemes, and several turbulence closure models is performed. The use of explicit filtering to reduce numerical errors is compared to results from the traditional LES approach. Filter functions that are smooth in spectral space are used, as the findings of this investigation are intended for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 23 publications
(32 reference statements)
4
157
0
3
Order By: Relevance
“…In practice, one frequently observes that the subfilter resolution r is taken as low as 1 or 2. 8,15,25,26 In such cases the smallest retained flow features are only marginally resolved and one may anticipate a significant effect from the numerical discretization. 9,16 Hence, even though the numerical filtering component can be controlled in principle by choosing r sufficiently large, virtually all large-eddy studies reported in literature contain dynamic contributions arising from the coarseness of the discretization.…”
Section: Decomposition Of the Numerical Turbulent Stress Tensormentioning
confidence: 99%
“…In practice, one frequently observes that the subfilter resolution r is taken as low as 1 or 2. 8,15,25,26 In such cases the smallest retained flow features are only marginally resolved and one may anticipate a significant effect from the numerical discretization. 9,16 Hence, even though the numerical filtering component can be controlled in principle by choosing r sufficiently large, virtually all large-eddy studies reported in literature contain dynamic contributions arising from the coarseness of the discretization.…”
Section: Decomposition Of the Numerical Turbulent Stress Tensormentioning
confidence: 99%
“…Inside the inner vessel, a pin bundle of 43 straight tubes, the alignment of which was the same as that of the Japanese prototype fast breeder reactor 'Monju' but rotated by an angle of 24 , was implemented. Figure 2 depicts the test section of the pin bundle.…”
Section: Swat-1r Experimentsmentioning
confidence: 99%
“…The angle of 24 was chosen so as to maximize the influence of the reacting zone on the neighboring tubes based on the previous observation.…”
Section: Swat-1r Experimentsmentioning
confidence: 99%
“…Indeed, the filter G to consider in practical simulations is a composition of the convolution filter L and the projective grid filter, referred to as P such that G = (L • P) , thereby embodying the explicit LES filter L and the implicit projective grid filter P [2,3], represented by a hat. In the sequel, the focus is put on the particular case where implicit grid filtering is the only effective filter.…”
Section: Grid Filter Modelsmentioning
confidence: 99%